LA LETTERA DI GIACOMO E L'ENIGMA DEL SUO TEMPO: Spunti storico-esegetici per un'ipotesi di datazione = THE LETTER OF JAMES AND THE ENIGMA OF HIS TIME : Historical-exegetical hints for a dating hypothesis. - D'Incà, Alberto (Rivista di storia del cristianesimo, 2020)
This paper aims to formulate a dating proposal of the Letter of James starting from a historical and exegetical analysis. As is known, during the last century many scholars saw this letter as one of the most ancient Christian writings, but currently others place it at the end of the first century CE or at the beginning of the second. These results, however, could be discussed again by focusing on the role of "faith" and "works" as depicted in Paul and James. A comparison between Rom 4:3 and Jas 2:23, indeed, suggests the dependence of James on Romans and not directly on Gen 15,6LXX: then, the terminus post quem of James has been fixed immediately after 56-57. Instead, the terminus ante quem has been established around 80 or 90, since James does not seem to know the emergence of a Pauline epistolary corpus. This conclusion is strengthened by the use of the example of Rahab in Jas 2:25, against which Heb 11,31 probably replies. Finally, the silence of James about the destruction of the Second Temple - if compared with the Jewish and Christian apocalyptic literature written by the end of the first century, together with the subsequent rabbinic theology concerning the Temple - allows to place the letter between 60 and 70 of the first century CE.